The impact of illegal online loans on student financial well-being and academic persistence - Wirawan, Logan Gunadi; Puteri, Ni Made Martini (Penelitian Ilmu Pengetahuan Sosial, 2025)
Background: The increasing prevalence of illegal online lending (pinjol) in Indonesia has raised concerns regarding its impact on students. Despite their status as educated individuals, many students face financial hardships that push them to seek alternative financial solutions, including illegal online loans. This research explores the factors leading students to use illegal online loans, the victimization process, and the long-term consequences on their academic and financial well-being. Methods: This study employs a qualitative research approach using a critical criminology framework to analyze the structural factors contributing to student victimization. Data were collected through structured interviews with seven students from different universities in Indonesia, all of whom had firsthand experience as illegal online loan users. Findings: Many students refrain from reporting their cases due to fear of social stigma, legal repercussions, and the perception that authorities may not take their complaints seriously. Students face financial strain due to tuition fees, living expenses, and societal expectations to be independent. Many are forced to seek quick financial solutions, leading them to illegal lending platforms. Victims often face intimidation and threats from debt collectors, including exposure of personal information. Conclusions: Illegal online loans create significant financial, psychological, and academic challenges for students. The exploitative nature of these loans exacerbates existing economic inequalities, forcing students into cycles of debt and distress. Novelty/Originality of this Article: This study offers a new perspective on the role of financial stress and social expectations in student involvement with illegal online lending. Unlike previous research that focuses solely on digital lending regulation, this study examines the personal experiences of student borrowers and the structural factors contributing to their financial victimization. The findings provide valuable insights for policymakers, financial institutions, and educators in developing preventive strategies to reduce student dependency on illegal online loans.